An evaluation of the use of olanzapine pamoate depot injection in seriously violent men with schizophrenia in a UK high-security hospital. (October 2014) - Baruch, Nina; Das, Mrigendra; Sharda, Amit; Basu, Amlan; Bajorek, Tom; Ross, Callum C; Sengupta, Samrat; Larkin, Fintan; Young, Susan
Background: Oral olanzapine is a well-established treatment for patients suffering from schizophrenia. Advantages of depot olanzapine may include improved compliance. However, it is expensive, causes metabolic side effects, and carries a risk of postinjection syndrome. Clinical trials have shown olanzapine pamoate to be effective, but further work is needed in this area. This study was a retrospective service evaluation, carried out in a high-security hospital, where the majority of patients have complex, treatment resistant schizophrenia spectrum disorder and a very high propensity for violence. Compliance is a significant problem, both in the high-security setting and on discharge. There has been no previous published work that the authors are aware of evaluating the effects of olanzapine pamoate in this subgroup of patients. Methods: The aim of the study was to evaluate the clinical efficacy of olanzapine pamoate, its effect on violence as well as its side effects, in a high-security setting for the first time. Anonymized patient records were used to identify the main outcome measure and clinical global improvement, and to ascertain secondary outcome measures which included seclusion hours, risk of violence and side effects. Metabolic parameters and number of incidents were also recorded. Eight patients were treated with olanzapine pamoate. Results: Six showed an improvement in symptoms, with an associated decrease in violence and number of incidents. Four showed an associated decrease in seclusion hours. Two showed an increase in body mass index and two showed an increase in glucose. Conclusions: The findings of this study are important in showing that all patients who responded to olanzapine pamoate also showed a decrease in violent behaviour. The potential anti-aggression effects of olanzapine pamoate may represent a very promising area for further work. A depot antipsychotic medication that reduces violence could have significant implications for management of high-security patients.